FEASIBILITY ANALYSIS OF GRID CONNECTED PHOTOVOLTAIC SYSTEM FOR RUPPUR, BANGLADESH (International Journal of Engineering Sciences & Management Research, 2018)
The smart grid is a suite of information-based applications made possible by increased automation of the electricity grid, as well as the underlying automation itself; this suite of technologies integrates the behavior and actions of all connected supplies and loads through dispersed communication capabilities to deliver sustainable, economic and secure power supplies. The focus of this paper is to familiarize with Smart Grid perspective to Bangladesh where the power system is very detailed, complex and quite aged. The agenda of this paper is to discuss about the significance and a detailed feasibility study of practical implementation of Smart Grid in Bangladesh. For the smart management system, we explore various management objectives, such as improving energy efficiency, profiling demand, maximizing utility, reducing cost, and controlling emission. We also explore various management methods to achieve these objectives. For the smart protection system, we explore various failure protection mechanisms which improve the reliability of the Smart Grid, and explore the security and privacy issues in the Smart Grid,